The Role of Artificial Intelligence in Scientific Research - Cheepi, Pullaiah. (AG Volumes, 2025)
In the rapidly developing area of artificial intelligence (AI), intelligence that can comprehend natural language, identify patterns, and make data-driven decisions—tasks that normally require human intellect—is developed. The many studies on artificial intelligence in scientific inquiry are reviewed in this article. It concluded that artificial Intelligence is reshaping scientific research by enhancing data analysis, accelerating results, and enabling the handling of large, complex datasets. Tools like Chat GPT streamline qualitative research by reducing manual effort and uncovering hidden patterns, making analysis more efficient and scalable. However, ethical, privacy, and governance concerns must be addressed, and AI should be viewed as a complement—not a replacement—for human cognitive input, particularly in theory development. With proper guidance, transparency, and understanding of AI capabilities, researchers can effectively integrate AI tools to advance scientific inquiry while maintaining the integrity and depth of traditional research methodologies.